1990
DOI: 10.1029/wr026i008p01749
|View full text |Cite
|
Sign up to set email alerts
|

Universal scaling of hydraulic conductivities and dispersivities in geologic media

Abstract: Neuman [1990] provided insight into a problem that has troubled groundwater hydrologists for at least the last ten years. He demonstrated that a fractal model appears to explain the scaling phenomenon of heterogeneity in aquifers, as measured by dispersivity values. The purpose of this comment is to put N euman's model into a geologic context. Neuman developed a universal scaling formula to relate dispersivity to the scale of observation but noted, "A major cause for local deviations from universal behavior ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

45
545
3
6

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 640 publications
(599 citation statements)
references
References 32 publications
(43 reference statements)
45
545
3
6
Order By: Relevance
“…They showed that this can be done at a given locale by calibrating a truncated variogram model to data observed on a given support in one region and by predicting the autocovariance structure of the corresponding field in regions that are either smaller or larger. They suggested that one may also venture to bridge across both window scales and locales by adopting the generalized Hurst coefficient H = 0.25, originally proposed by Neuman [1990], and other generalized variogram parameters derived in their paper.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that this can be done at a given locale by calibrating a truncated variogram model to data observed on a given support in one region and by predicting the autocovariance structure of the corresponding field in regions that are either smaller or larger. They suggested that one may also venture to bridge across both window scales and locales by adopting the generalized Hurst coefficient H = 0.25, originally proposed by Neuman [1990], and other generalized variogram parameters derived in their paper.…”
Section: Introductionmentioning
confidence: 99%
“…Their model predicts smoothly varying, monotonic parameter behavior. In similar concept, a fractal model is proposed by Neuman [1990], which exhibits a linear log-log relation between sample scale and parameter value, rendering the concept of RES meaningless. While fracture structure may be fractal, at least over some scale ranges in some types of geologic media, Wellman and Poeter [2005] found no such scale behavior using hydraulic head estimation of RES (HYRES), but we acknowledge fractal architectures were not considered.…”
Section: Representative Elementary Scalementioning
confidence: 99%
“…is assumed, which may be taken as the asymptotic limiting form of the dispersion tensor (Neuman, 1990). It should be noted that issues related to the scale dependence of dispersion are not considered.…”
Section: Process Model Equationsmentioning
confidence: 99%